Perbandingan Kinerja Perusahaan Dengan Pendekatan Balanced Scorecard Pada BPR Syariah - Angrum Pratiwi (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2015)
This research aims to discover the progress of BPRS in Yogyakarta by using balanced scorecard (BSC) approach. BSC is a concept of management that help to translate the company strategy into company activities. There are four aspects to be evaluated in the BSC: financial prospective, consumen, internal business, growth and learning. This research is a descriptive and comparative research. The author conducted fieldwork in two BPRS, which are BPRS Barokah Dana Sejahtera and BPRS Bangun Drajat Warga. The research sampel comprises financial aspect (fi- nancial report of 2012-2014); consumen aspect (400 respondents); growth and learning (69 respondents); and internal bussiness aspect (questioner and interview). There is not much difference between the two BPRS in their financial, consumen, growth and learning, and internal bussiness aspects. Yet, there is differences between the two in their NPF, KPMM, FDR, finance, profit–sharing, and DPK. In a nutshel, the research result shows that BPRS Barokah is greater in its growth thaks to a solid team work